TATA KELOLA ANGKUTAN KOTA OLEH DINAS PERHUBUNGAN KOTA BANDUNG DALAM MENINGKATKAN MINAT MASYARAKAT TAHUN 2024 - Nenden Nur Asri; Dede Sri Kartini; Tiyan Rahmanul Hakim (T JDP (JURNAL DINAMIKA PEMERINTAHAN), 2025)
Urban transportation governance in Bandung City still faces various challenges that directly impact the quality of public services and the fulfillment of citizens’ mobility rights. This study aims to analyze the implementation of urban transportation governance carried out by the Bandung City Transportation Agency, based on six core principles of good transportation governance according to Soejachmoen: responsibility, transparency, responsiveness, fairness, equity, and public participation. Primary data were collected through in-depth interviews with the government, namely the Transportation Agency, and with public transportation users. The findings indicate that the governance of urban transportation in Bandung City has not yet been optimal. Several indicators of the Minimum Service Standards as regulated in the Ministry of Transportation Regulation Number 29 of 2015 have not been fulfilled, such as clarity of fare information, route regularity, guarantees of passenger safety and comfort, as well as consistent supervision and enforcement of sanctions for violations. Improving urban transportation governance in Bandung requires concrete efforts through policy transparency, enhanced supervision, and the expansion of inclusive public participation.